2017
DOI: 10.5114/ceji.2017.70964
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of Moringa peregrina leaves, ex vivo and in vivo study

Abstract: This study was conducted to assess the in vivo and ex vivo immunomodulatory effect of the ethanol leaves extract of Moringa peregrina in Balb/c mice. For this study, five groups of 5 Balb/c mice were given a single acute subtoxic oral dose of the ethanolic extract at 1.13, 11.30, 23.40 and 113.4 mg/kg and the immunomodulatory effect was assessed on the 6th day following the ingestion. In the (non-functional) assessment, the effect of the extract on the body weight, relative lymphoid organ weight, splenic cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…When cells die, they rapidly lose the ability to convert the substrate to the product (blue colour) (Figure 5b). Al‐Majali et al, (2017) showed in an in vivo study that ethanolic extract increased spleen cell number with oral administration of Moringa peregrina leaves. Moreover, this proliferation effect could have been the result of lymphocyte migrations from the spleen to the circulatory system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When cells die, they rapidly lose the ability to convert the substrate to the product (blue colour) (Figure 5b). Al‐Majali et al, (2017) showed in an in vivo study that ethanolic extract increased spleen cell number with oral administration of Moringa peregrina leaves. Moreover, this proliferation effect could have been the result of lymphocyte migrations from the spleen to the circulatory system.…”
Section: Resultsmentioning
confidence: 99%
“…MoSE) with viable cells results in a signal proportional to the number of viable cells found in the culture (pink colour). When cells die, they rapidly lose the ability to convert the substrate to the product (blue colour) (Figure5b) Al-Majali et al, (2017). showed in an in vivo study that ethanolic extract increased spleen cell number with oral administration of Moringa peregrina leaves.…”
mentioning
confidence: 99%
“…Generally, extracts with high phenolic content and high antioxidant activities also exhibit high antimicrobial activities [ 46 , 54 , 55 ]. The ethanol and methanol extracts of the pomegranate peels showed the highest inhibition activity against the microbial strains Pseudomonas aeruginosa , Klebsiella pneumoniae , and Micrococcus luteus and the fungal strain Candida albicans .…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in rabbits (Jiwuba et al, 2016, El-Badawi et al al., 2016, El-Gindy et al, 2017& salem et al, 2020 and in rats (Adedapo et al, 2005, Gupta et al, 2010, Isitua & Ibeh, 2013and Asomugha et al, 2015 but the increase in WBC count was stastically significant. Also, Al-Majali et al (2017) showed that supplementation of ethanolic Moringa peregrina extract to rats resulted in a significant increase in total WBC counts in peripheral blood. Lamou et al, 2016, Kasolo et al, 2010 attributed the increase in WBCs to decreased oligosaccharides in Moringa oleifera leaves.…”
Section: Iii-effect Of Mol and Moscmentioning
confidence: 98%
“…Previous research reports concluded that M. oleifera is an immunomodulatory agent that can stimulate the production of IgG, IgM and IgA (Al-Badawi et al, 2016, El Gendy et al, 2017, Al-Majali et al, 2017and Abd-Elhakim et al, 2018 as well as the aqueous extract of M. oleifera showed a strong immune-modulating effect that could modulate B-cell activation and stimulate the production of IgM, IgA and IgG level after administration (Ojeka et al 2016), and T cells where it will result for induction of IL 10 production (Fard et al 2015;Tan et al 2015) and inhibit production of TNFα, IL-6, IL-8 (Kooltheat et al 2014) andIL-2 (Sashidhara et al 2009).…”
Section: Ii-effect Of Mol and Mosc Supplementation In Rations Of Bark...mentioning
confidence: 99%